2022
DOI: 10.1097/bot.0000000000002291
|View full text |Cite
|
Sign up to set email alerts
|

Streamlining Trauma Research Evaluation With Advanced Measurement (STREAM) Study: Implementation of the PROMIS Toolbox Within an Orthopaedic Trauma Clinical Trials Consortium

Abstract: Information System (PROMIS) has developed item banks, short forms, and computer-adaptive tests (CATs) to help standardize measurement for important patient-reported outcome domains. These tools have the potential to revolutionize outcome measurement in clinical research through greater assessment precision while reducing response burden. Perceived implementation challenges include the need for CAT software, mobile technology, and Internet access. Here, we present preliminary results examining the feasibility o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…To our knowledge, no other studies have evaluated the test-taker burden of Pediatric PROMIS CATs in a similar pediatric orthopaedic population. However, several studies have found similar TTCs in adults 16. In a cross-sectional study of completion time for 4 PROMIS CATs in adults (Pain Interference, Physical Function [lower extremity], Upper Extremity, and Depression) at a single sports medicine clinic, Omar Kadri et al12 found a mean TTC of 0.83 minutes per PROMIS CAT.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…To our knowledge, no other studies have evaluated the test-taker burden of Pediatric PROMIS CATs in a similar pediatric orthopaedic population. However, several studies have found similar TTCs in adults 16. In a cross-sectional study of completion time for 4 PROMIS CATs in adults (Pain Interference, Physical Function [lower extremity], Upper Extremity, and Depression) at a single sports medicine clinic, Omar Kadri et al12 found a mean TTC of 0.83 minutes per PROMIS CAT.…”
Section: Discussionmentioning
confidence: 92%
“…However, several studies have found similar TTCs in adults. 16 In a cross-sectional study of completion time for 4 PROMIS CATs in adults (Pain Interference, Physical Function [lower extremity], Upper Extremity, and Depression) at a single sports medicine clinic, Omar Kadri et al 12 found a mean TTC of 0.83 minutes per PROMIS CAT. Similarly, Bernstein et al 3 found a mean TTC of 0.86 minutes when evaluating the same 4 PROMIS CATs for 20,489 unique visits at a single academic medical center hand clinic.…”
Section: Discussionmentioning
confidence: 99%